(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Medical thermography, particularly digital infrared thermal imaging, has emerged as a promising non-invasive diagnostic modality in neurology and pain medicine. Neuropathic pain and nerve dysfunction are frequently associated with abnormalities in autonomic regulation, vascular control, and tissue metabolism, all of which influence skin temperature distribution. Infrared thermography detects these changes by measuring emitted infrared radiation from the body surface. The physiological basis, clinical applications, diagnostic significance, advantages, limitations, and future perspectives of medical thermography in detecting neuropathic pain and nerve dysfunction.